Microplasticity of 15Kh2NMFA vessel steel in a stress-strain state during magnetic treatment - Chernyak, N.A.; Sokolenko, V.I. (Вопросы атомной науки и техники, 2022)
Earlier it was found that the treatment of pre-strained ferrite-pearlite vessel steel 15Kh2NMFA, welded joints of this steel by alternating magnetic field of industrial frequency leads to a decrease in the level and alignment of the stress field’s relief and significantly improves the complex of physical and mechanical properties. When non-stationary magnetic fields are applied to a structurally inhomogeneous ferromagnetic material, several different mechanisms of rearrangement of the domain and defect structure can act. In this work, we propose a model of dislocation system response of ferromagnetic in a stress-strain state to a magnetic effect, based on the microscopic properties of dislocations in a mechanically unstable state. Раніше було встановлено, що обробка попередньо деформованих зразків корпусної сталі 15Х2НМФА, зварних з'єднань цієї сталі змінним магнітним полем промислової частоти суттєво покращує комплекс фізико-механічних властивостей, призводить до зниження рівня та вирівнювання рельєфу полів внутрішніх напруг. Метою цієї роботи була побудова моделі відгуку системи дислокацій феромагнетика в напружено-деформованому стані на магнітний вплив, заснований на мікроскопічних властивостях дислокацій в механічно нестійкому стані. Ранее было установлено, что обработка предварительно деформированных образцов корпусной стали 15Х2НМФА, сварных соединений этой стали переменным магнитным полем промышленной частоты существенно улучшает комплекс физико-механических свойств, приводит к снижению уровня и выравниванию рельефа полей внутренних напряжений. Целью настоящей работы являлось построение модели отклика системы дислокаций ферромагнетика в напряженно-деформированном состоянии на магнитное воздействие, основанной на микроскопических свойствах дислокаций в механически неустойчивом состоянии.